Attractiveness of VET in China: a study on secondary vocational students and their parents - Hao, Tiancong [Verfasser]; Pilz, Matthias [Verfasser] (My University, 2021)
“The attractiveness of vocational education and training in China is becoming increasingly important for both policy makers and practitioners. This study examines the perceptions of secondary vocational students and their parents, about the attractiveness of vocational education and training in China. For data collection, 54 Students and 27 parents were selected from three kinds of vocational programmes in Shanghai. The results show that general high schools are perceived to be far more attractive than secondary vocational schools. One major finding is that the attractiveness of the three programmes that are part of this study increases as the programme length increases. However, it is not the higher diploma, but rather the potential long-term career promotion space in the labour market, that really influenced students’ priority for higher education.” (authors’ abstract)
Keywords: S System beruflicher Bildung; P 2.3 Auszubildende; G 1.3.2 Bildungsverhalten und -verläufe; I 2.3.4 Asien; 370; Berufsbildungssystem; Berufsbildung; Attraktivität; Berufsschüler; Eltern; Bildungsaspirationen; Befragung; China